Reinventare il paesaggio urbano. Approccio “di politiche” e place-making Paolo Cottino - Cottino, Paolo (Ri-Vista. Research for landscape architecture, 2015)
In ‹‹Giustizia e Bellezza››, published in 2007 by Bollati Boringhieri, Luigi Zoja offers articulate arguments for modern distance between ethics and aesthetics. This is a contradiction of the original unity of ancient Greece, in which they were ‹‹two sides of the same quality: virtue and excellence››. Our reading of the essay is based on these materials, which stimulate possible innovative influences about the sense of landscape in spatial plans and projects. In Luigi Zoja dialogue there are some elements that confirm the potential of the book. Understanding contemporary landscapes from the point of view of the imbalances that they somatized because of cultural separation of Justice and Beauty, may allow us a deeper, mature and effective cognitive and planning interpretation.